Nilai-Nilai Pancasila Dalam Buku Bacaan Berjenjang (B3) USAID Seri F - Musyafa, Ahmad Arif (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
This study aims to describe the content of Pancasila values ​​and describe the Presentation Techniques in the Leveled Reading Book of the USAID Series F. This research is a qualitative descriptive study using content analysis methods, with reading, listening, and note-taking data collection techniques (BSC). ). The results of this study showed that the values ​​of Pancasila contained in the Leveled Reading Book of the USAID Series F included several values ​​out of 36 Pancasila values. In addition, the techniques used in presenting the values ​​of Pancasila include action techniques, words techniques, appearance techniques, other people's commentary techniques, and author commentary techniques. Based on the results of the study, it can be stated that the book contains the values ​​of Pancasila and uses the presentation of values ​​that can help the development of the character and character of the readers, especially for children readers. So that this reading book can be recommended as a reading book in elementary schools. Keywords: Values ​​of Pancasila, Delivery Techniques, the Leveled Reading Book of the USAID Series F